IDENTIFIKASI ANGKA KECUKUPAN GIZI DAN STRATEGI PENINGKATAN GIZI KELUARGA DI KOTA PROBOLINGGO (STUDI KASUS DI KECAMATAN KEDOPOK DAN MAYANGAN) - SHINTA, AGUSTINA (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2010)
The objective of the research is to identify the nutrition adequacy rate in the city ofProbolinggo and the strategy to increase such rate. The adequacy of nutrition can be viewed from the state of nutrition. State of nutrition is a body condition as a result of the balance between food intake and how it is used by the body. This can be measured through various dimensions and each element of nutrition both micro as well as macro elements of nutrition. The macro element of nutrition is energy,protein and fat while micro element of nutrition is calcium, phosphor, zinc and vitamin C. Information on the component of food being consumed is obtained through people’s “recall one-day consumption” interview approach.